A Study on Performance Evaluation of Domestic Water Purifiers - Saini, Ravinder Kaur (My University, 2012)
A study on the performance of domestic water purifier was conducted between Jan- May 2012. Purifiers aquaguard, Green RO, Pureit, and Kent RO, found installed at TU campus and Aquafresh at Anand Nagar were selected for the study. The Raw water available and treated water generated was analysed for physic-chemical analysis. It was observed that raw water at Anand Nagar was more unhygienic compared to that of campus. Green RO and Kent RO showed maximum removal of water contaminants. Performance of purifiers was aggregated as water quality index (WQI).WQI values declined for treated water quality compared to raw water, indicating that the treatment went in purifier.
Keywords: Water; Purification; Performance